A New RTL Design Approach for a DCT/IDCT-Based Image Compression Architecture using the mCBE Algorithm - Rachmad Vidya Wicaksana Putra; Rella Mareta; Nurfitri Anbarsanti; Trio Adiono (Journal of ICT Research and Applications, 2012)
In  the  literature, several approaches  of  designing  a  DCT/IDCT-based image compression system have been proposed.  In this paper,  we present a new RTL design approach with as main  focus developing a  DCT/IDCT-based image compression  architecture  using  a  self-created  algorithm.  This  algorithm  can efficiently  minimize  the  amount  of  shifter -adders  to  substitute  multiplier s.  We call  this  new  algorithm  the  multiplication  from  Common  Binary  Expression (mCBE)  Algorithm. Besides this algorithm, we propose alternative quantization numbers,  which  can  be  implemented  simply  as  shifters  in  digital  hardware. Mostly, these numbers can retain a good compressed-image quality  compared to JPEG  recommendations.  These  ideas  lead  to  our  design  being  small  in  circuit area,  multiplierless,  and  low  in  complexity.  The  proposed  8-point  1D-DCT design  has  only  six  stages,  while  the  8-point  1D-IDCT  design  has  only  seven stages  (one  stage  being  defined as  equal  to  the  delay  of  one  shifter  or  2-input adder). By using the pipelining method, we can achieve a high-speed architecture with latency as    a  trade-off consideration. The  design has been synthesized and can reach a speed of up to 1.41ns critical path delay (709.22MHz).